ANALISIS KINERJA UNDERWRITER DALAM MENENTUKAN CALON PESERTA PADA PRODUK ASURANSI MOBILKOE (Studi Pada PT Asuransi Umum Bumiputera 1967 Cabang Serang) - Ikin Ainul Yakin; Eva Nurhabibah (UIN Sultan Maulana Hasanuddin Banten, 2020)
Every company really needs workers as actors who can carry out company activities in order to achieve the expected goals for it is expected that a worker who has quality human resources. Unfortunately this has not been matched by quality workforce. Often the opening of a branch or new Islamic insurance division is only supported by a limited number of workers because the need for Underwriter-certified Underwriters is still lacking. Development and marketing of insurance products must be supported by the availability of human resources that enable the good implementation of Underwriter performance Underwriter performance. in sharia insurance has an important role because he determines whether insurance coverage is acceptable or not Based on the results of the analysis conducted by researchers on research, there is a role for Underwriters' performance in determining prospective participants in mobilkoe insurance products, namely: improving service quality, applying quality of human resources in performance, risk identification, risk assessment, risk estimation and acceptability, and risk sharing, as well as the obstacles encountered by the Underwriters in determining the prospective participants in mobilkoe insurance products are the availability of incomplete participant data, data on previous participant experience and prospective participants do not provide the desired benefit budget, while the solution is to contact Agent in order to obtain additional information needed by an Underwriter.